Bhasan Char: How the “Floating Island” Sinks International Refugee Protections - Yaseen Morshed (Washington University Global Studies Law Review, 2025)
Without warning, Yusuf Ali’s children were taken from him and transferred to Bhasan Char, a small island in the Bay of Bengal. Yusuf, a Rohingya refugee living in the Cox’s Bazar district of Bangladesh, learned from his daughters that Bhasan Char felt like “an island jail in the middle of the sea.”But if Yusuf wanted to stay with his children, he only had one option: relocate to Bhasan Char himself. Bhasan Char, or the “floating island,” is a sedimentary island that did not exist twenty years ago. Today the island is home to thousands of Rohingya refugees—many who are children, like Yusuf’s daughters—and thousands more will be relocated. Sitting just six feet above sea level and spanning an area of fifteen square miles, Bhasan Char frequently experiences extreme weather and intense flooding. As a result, the island was used only as a brief stopping point for local fishermen for many years after its formation,. However, this limited use ended in 2017 when Bangladesh designated Bhasan Char for Rohingya resettlement. The designation was part of a refugee relocation plan, proposed by Bangladesh’s government after thousands of Rohingya—who were facing violent persecution in Myanmar—crossed the Bangladeshi border into Cox’s Bazar. These refugees sought shelter at the refugee camps scattered along the eastern border of Cox’s Bazar, joining an estimated 200,000 Rohingya who were displaced during earlier waves of violence.
Keywords: Rohingya; Bhasan Char; Bangladesh; Myanmar; Rohingya Refugee; Refugee Relocation